Upregulation of long non-coding RNA SNHG16 promotes diabetes-related RMEC dysfunction via activating NF-κB and PI3K/AKT pathways - Fei Cai; Huanzong Jiang; Yan Li; Qin Li; Chao Yang (Elsevier, 2021)
Diabetic retinopathy (DR) is a severe diabetes-induced eye disease, in which its pathological phenomena basically include abnormal proliferation, migration, and angiogenesis of microvascular endothelial cells in the retina. Long non-coding RNAs (lncRNAs) have been proven to be important regulators in various biological processes, but their participation in DR remains largely undiscovered. In the present study, we aimed to unveil the role of lncRNA small nucleolar RNA host gene 16 (SNHG16) in regulating the functions of human retinal microvascular endothelial cells (hRMECs) under a high-glucose (HG) condition. We found that SNHG16 expression was significantly upregulated in hRMECs treated with HG. Functionally, SNHG16 could facilitate hRMEC proliferation, migration, and angiogenesis. Moreover, SNHG16 was associated with nuclear factor κB (NF-κB) and phosphatidylinositol 3-kinase (PI3K)/AKT pathways. Mechanistically, SNHG16 could promote hRMEC dysfunction by sequestering microRNA (miR)-146a-5p and miR-7-5p to act as a competing endogenous RNA (ceRNA) with interleukin-1 receptor-associated kinase 1 (IRAK1) and insulin receptor substrate 1 (IRS1). In conclusion, our results illustrated the potential role of SNHG16 in facilitating hRMEC dysfunction under HG treatment, providing a novel approach for DR therapy.